The Acceptability of Occupational Therapy Using Zones of Regulation™ Concepts in an Equine Environment to Autistic Children - Jacqueline M. Browne; Sarah Jean Reega; Ellen M. Rankins; Arlene A. Schmid; B. Caitlin Peters (Behavioral Sciences)
Autistic children often have impaired self-regulation which can impact daily functioning and life outcomes. Occupational Therapy Using Zones of Regulation™ Concepts in an Equine Environment (OT-ZOR-Equine) is a standardized intervention that integrates both the Zones of Regulation™ curriculum and horses into occupational therapy to address self-regulation in autistic children. We aimed to assess the acceptability of OT-ZOR-Equine to participating autistic children. A qualitative descriptive research study was conducted with six autistic children ages 7–9 years who received ten weeks of OT-ZOR-Equine. Children participated in semi-structured interviews that used questions guided by the Theoretical Framework of Acceptability. We analyzed interview transcripts using directed content analysis. Autistic children found OT-ZOR-Equine to be generally acceptable. The children especially enjoyed horse riding but found the Zones of Regulation™ curriculum and certain aspects of riding to be less acceptable. Tailoring OT-ZOR-Equine to integrate each client’s preferences and needs may make this intervention more acceptable to autistic children. The findings of this study support the continued use of and research on OT-ZOR-Equine or similar occupational therapy interventions that integrate horses to influence self-regulation in autistic children.